Description of a new species of Eulepethus (Annelida, Eulepethidae) from the northern South China Sea, and comments on the phylogeny of the family - Zhang, Jinghuai; Zhang, Yanjie; Osborn, Karen; Qiu, Jian-Wen (Zootaxa, 2017)
Eulepethidae is a family of scale-bearing polychaetes. Although members of this family are common inhabitants of tropical and subtropical coastal waters, their diversity is low, with only 22 recognized species in six genera. Here we describe Eulepethus nanhaiensis sp. nov. based on 12 specimens collected from the coastal waters of the northern South China Sea. This new species can be distinguished from Eulepethus hamifer, the only previously described species in this genus, by having up to two spade-shaped lateral processes in some of the anterior elytrae, a blunt-tipped acicular chaeta in the neuropodia of segment 3, and a pair of non-overlapping elytrae in each posterior segment. Phylogenetic analysis indicates that Grubeulepis and Mexieulepis are sister genera, and these two genera form the sister clade of Eulepethus.